Risk of requiring a wheelchair in primary progressive multiple sclerosis: Data from the ORATORIO trial and the MSBase registry. (6th May 2021) - Butzkueven, Helmut; Spelman, Tim; Horakova, Dana; Hughes, Stella; Solaro, Claudio; Izquierdo, Guillermo; Kubala Havrdová, Eva; Grand'Maison, Francois; Prat, Alexandre; Girard, Marc; Hupperts, Raymond; Onofrj, Marco; et al.
Abstract: Background and purpose: Reaching Expanded Disability Status Scale (EDSS) ≥7.0 represents the requirement for a wheelchair. Here we (i) assess the effect of ocrelizumab on time to EDSS ≥7.0 over the ORATORIO (NCT01194570) double‐blind and extended controlled periods (DBP+ECP), (ii) quantify likely long‐term benefits by extrapolating results, and (iii) assess the plausibility of extrapolations using an independent real‐world cohort (MSBase registry; ACTRN12605000455662). Methods: Post hoc analyses assessing time to 24‐week confirmed EDSS ≥7.0 in two cohorts of patients with primary progressive multiple sclerosis (baseline EDSS 3.0–6.5) were investigated in ORATORIO and MSBase. Results: In the ORATORIO DBP+ECP, ocrelizumab reduced the risk of 24‐week confirmed EDSS ≥7.0 (hazard ratio = 0.54, 95% confidence interval [CI]: 0.31–0.92; p = 0.022). Extrapolated median time to 24‐week confirmed EDSS ≥7.0 was 12.1 and 19.2 years for placebo and ocrelizumab, respectively (7.1‐year delay [95% CI: −4.3 to 18.4]). In MSBase, the median time to 24‐week confirmed EDSS ≥7.0 was 12.4 years. Conclusions: Compared with placebo, ocrelizumab significantly delayed time to 24‐week confirmed wheelchair requirement in ORATORIO. The plausibility of the extrapolated median time to reach this milestone in the placebo group was supported by observed real‐world data from MSBase. Extrapolated benefits for ocrelizumab over placebo could represent a truly meaningful delay in loss of ambulation and independence. Abstract : Extrapolated data from the ORATORIO trial suggest ocrelizumab treatment delays the median time to requiring a wheelchair by 7.1 years versus placebo. Similar disability trajectories observed in real‐world data from the MSBase registry and initial data from the ORATORIO open‐label extension support the plausibility of these extrapolations.